2021
DOI: 10.1111/jerd.12824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adjacent teeth on the accuracy of intraoral scanning systems for class II inlay preparation

Abstract: Objective: This study aimed to evaluate the influence of the presence of adjacent teeth on the accuracy of intraoral scanning (IOS) systems for class II inlay preparation. Materials and Methods:The mesio-occlusal inlay preparation was prepared in an anatomical model of the maxillary molar. The prepared tooth was secured to a typodont with the mesial adjacent tooth removed or in situ. Ten digital impressions of the inlay preparation were acquired using three IOS systems (CEREC Primescan, 3Shape TRIOS 3, and Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…This finding is in accordance with a previous study comparing IOS devices for preparations [14]. On the other hand, another study on inlay preparations described that Primescan (Dentsply-Sirona) had the best trueness [20]. Regarding IOS of dental arches, it was found that the IOS devices included by the studies varied considerably, which prevented this review from drawing any conclusions about which devices actually have the best trueness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in accordance with a previous study comparing IOS devices for preparations [14]. On the other hand, another study on inlay preparations described that Primescan (Dentsply-Sirona) had the best trueness [20]. Regarding IOS of dental arches, it was found that the IOS devices included by the studies varied considerably, which prevented this review from drawing any conclusions about which devices actually have the best trueness.…”
Section: Discussionsupporting
confidence: 89%
“…After initial screening of the publications using titles, abstracts and keywords, 13 articles were considered within the inclusion criteria. After the application of exclusion criteria, a total of nine studies (6 in vitro and 3 in vivo) were finally identified (Figure 1) as eligible to be discussed [19][20][21][22][23][24][25][26][27]. All papers assessed were available on both databases used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Today, IOS systems have the advantages of ease of use, ergonomic handling, quick scanning, and reliability. Several studies have confirmed the accuracy of IOS systems for multiple applications 1–8 . However, despite the abundance of studies on the accuracy of IOS systems, there is considerable disparity in their designs 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…The variations can be related to the scanning span, the number of units, scanned substrate material and design, and the condition of the scanned teeth 10 . One of the features that have not been fully investigated is the implication of tooth preparation type on the accuracy of IOS 1–3,9,13–15 . Variations in preparation types and designs, such as crown, onlay, and inlay, may interfere with the scanning process and the capturing of the preparation surface details 16–21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation